PELAKSANAAN ASURANSI KEBAKARAN PADA PT. ASURANSI TAKAFUL UMUM CABANG PADANG - Novalia Indra (IAIN Batusangkar, 2015)
This qualitative descriptive research was purposed at describing the implementation of fire insurance in PT Insurance Takaful Umum Padang branch. The techniques of collecting data in this research were interview and study document. This research found that the implementation of fire insurance in PT insurance Takaful umum Padang branch was begun by filling the data in the application letter of fire insurance (SPPAK). Then PT insurance Takaful umum Padang branch produced the appointment in PSKI. The barrier of claim was happened because the consumer did not read and understand the appointment in PSKI. Keywords: Implementation, Fire Insurance, PT Insurance Takaful Umum Padang Branch